Personalized Cardiovascular Regenerative Medicine: Targeting the Extreme Stages of Life - Madeddu, Paolo; Avolio, Elisa; Alvino, Valeria Vincenza; Santopaolo, Marianna; Spinetti, Gaia (Frontiers in Cardiovascular Medicine, 2019)
Cardiovascular regenerative medicine is an exciting new approach that promises to change the current care of million people world-wide. Major emphasis was given to the quality and quantities of regenerative products, but recent evidence points to the importance of a better specification of the target population that may take advantage of these advanced medical treatments. Patient stratification is an important step in drug development. Tailoring treatment to the patient’s specificity allowed significant improvement in cancer therapy, but personalised regenerative medicine is still at the initial stage in the cardiovascular field. For example, new-borns with a congenital heart condition and elderly people require dedicated therapeutic approaches, which adapt to their lifetime needs. In these people, personalised treatments may overcome the benefits delivered by standard protocols. In this review, we provide insights into these extreme stages of life as potential targets for cardiovascular reconstitution.